An investigation into musicians' thoughts and perceptions during performance. (June 2014) - Clark, Terry; Lisboa, Tânia; Williamon, Aaron
Given the current state of understanding surrounding musicians' experiences while performing, this study sought to investigate musicians' thoughts and perceptions during performances and the perceived impact their evaluation of those thoughts and perceptions has on their subsequent musical activities. Twenty-nine student and professional classical musicians were interviewed concerning factors perceived to contribute to the quality of performances, experiences prior to and during performances, and their responses to performances. Self-perceived successful performances were often connected with feelings of sufficient preparation and positive mind-sets, and presented a high yet attainable level of challenge. Less successful performances were typically linked with inadequate preparation, negative mental outlooks, frustration, and lack of enjoyment during the performance itself. Furthermore, the results pointed to the relevance of facilitative versus debilitative perfectionism, locus of control, interpretation of anxiety symptoms, and the interaction between self-talk, self-efficacy, and performance quality to musicians' performance experiences and satisfaction.